Effects of Lowering Body Temperature via Hyperhydration, With and Without Glycerol Ingestion and Practical Precooling on Cycling Time Trial Performance in Hot and Humid Conditions - Ross, MLR; Jeacocke, NA; Laursen, PB; Martin, DT; Abbiss, Chris R; Burke, LM (BioMed Central Ltd., 2012)
Background Hypohydration and hyperthermia are factors that may contribute to fatigue and impairment of endurance performance. The purpose of this study was to investigate the effectiveness of combining glycerol hyperhydration and an established precooling technique on cycling time trial performance in hot environmental conditions. Methods Twelve well-trained male cyclists performed three 46.4-km laboratory-based cycling trials that included two climbs, under hot and humid environmental conditions (33.3 ± 1.1°C; 50 ± 6% r.h.). Subjects were required to hyperhydrate with 25 g.kg-1 body mass (BM) of a 4°C beverage containing 6% carbohydrate (CON) 2.5 h prior to the time trial. On two occasions, subjects were also exposed to an established precooling technique (PC) 60 min prior to the time trial, involving 14 g.kg-1 BM ice slurry ingestion and applied iced towels over 30 min. During one PC trial, 1.2 g.kg-1 BM glycerol was added to the hyperhydration beverage in a double-blind fashion (PC+G). Statistics used in this study involve the combination of traditional probability statistics and a magnitude-based inference approach. Results Hyperhydration resulted in large reductions (−0.6 to −0.7°C) in rectal temperature. The addition of glycerol to this solution also lowered urine output (330 ml, 10%). Precooling induced further small (−0.3°C) to moderate (−0.4°C) reductions in rectal temperature with PC and PC+G treatments, respectively, when compared with CON (0.0°C, P<0.05). Overall, PC+G failed to achieve a clear change in cycling performance over CON, but PC showed a possible 2% (30 s, P=0.02) improvement in performance time on climb 2 compared to CON. This improvement was attributed to subjects’ lower perception of effort reported over the first 10 km of the trial, despite no clear performance change during this time. No differences were detected in any other physiological measurements throughout the time trial. Conclusions Despite increasing fluid intake and reducing core temperature, performance and thermoregulatory benefits of a hyperhydration strategy with and without the addition of glycerol, plus practical precooling, were not superior to hyperhydration alone. Further research is warranted to further refine preparation strategies for athletes competing in thermally stressful events to optimize health and maximize performance outcomes.
Keywords: Euhydration; Hypothermia; Self-paced endurance performance; Perception of effort; Environmental heat gain; Metabolic heat gain; Heat dissipation